2010
DOI: 10.1073/pnas.1017419108
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus nuclear antigen 3C regulated genes in lymphoblastoid cell lines

Abstract: EBV nuclear antigen 3C (EBNA3C) is an essential transcription factor for EBV transformed lymphoblast cell line (LCL) growth. To identify EBNA3C-regulated genes in LCLs, microarrays were used to measure RNA abundances in each of three different LCLs that conditionally express EBNA3C fused to a 4-OH-Tamoxifen-dependent estrogen receptor hormone binding domain (EBNA3CHT). At least three RNAs were assayed for each EBNA3CHT LCL under nonpermissive conditions, permissive conditions, and nonpermissive conditions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 69 publications
6
49
1
Order By: Relevance
“…Conversion of Affymetrix probe set identities into Ensembl gene codes identified 47 genes that were downregulated (see Table S1 in the supplemental material) and 122 genes that were upregulated by EBNA 3C by 2-fold or more (see Table S2 in the supplemental material). EBNA 3C was previously reported to upregulate expression of the B-cell activation marker complement receptor 2 (CR2, CD21) in BJAB E3C-4 cells and in an EBNA 3C transcomplemented LCL (50,56). Our analysis confirmed that this gene was upregulated 16-fold at the mRNA level, providing a good validation control for our study (see Table S2 in the supplemental material).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Conversion of Affymetrix probe set identities into Ensembl gene codes identified 47 genes that were downregulated (see Table S1 in the supplemental material) and 122 genes that were upregulated by EBNA 3C by 2-fold or more (see Table S2 in the supplemental material). EBNA 3C was previously reported to upregulate expression of the B-cell activation marker complement receptor 2 (CR2, CD21) in BJAB E3C-4 cells and in an EBNA 3C transcomplemented LCL (50,56). Our analysis confirmed that this gene was upregulated 16-fold at the mRNA level, providing a good validation control for our study (see Table S2 in the supplemental material).…”
Section: Resultssupporting
confidence: 76%
“…They comprise the genes encoding the heterodimeric B-lymphocyte ␣4␤1 integrin receptor (ITGB1 and ITGA4) and the novel ␣4␤1 integrin ligand, ADAM28 (7,31), along with a related gene, ADAMDEC1, located in the same gene cluster, that is downregulated during tumorigenesis (6,25). In support of our results, while this work was in progress, EBNA 3C was reported to repress ITGA4 expression in transcomplemented LCLs, although in another BL cell background EBNA 3C is required to maintain ITGA4 expression (52,56). Loss of EBNA 3B expression in LCLs results in downregulation of ITGB1, implicating EBNA 3B as a positive regulator of ITGB1 (52) ( Table 3).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…3B). Thus, the EBNA3 proteins, despite their roles in the repression of multiple cell genes (19)(20)(21)(22)(23)(24)(25), bind predominantly at genomic sites bearing marks of transcriptionally active chromatin.…”
Section: Genome-wide Binding Analysis Of Ebna3 Proteins In Lclsmentioning
confidence: 99%
“…Although EBNA3s bind an RBPJ domain that is distinct from the EBNA2/ICN binding site, they nevertheless limit EBNA2 activation by competing for RBPJ binding (15)(16)(17)(18). In LCLs and Burkitt lymphoma tumor cells, the EBNA3 proteins have been shown to regulate distinct but extensively overlapping sets of cell genes (19)(20)(21)(22)(23)(24)(25)(26). EBNA3 proteins have been implicated in the pathogenesis of Burkitt lymphoma and in attenuating an antiproliferative DNA damage response during EBV transformation of primary B lymphocytes (19,(27)(28)(29).…”
mentioning
confidence: 99%